The feasibility of small-caliber veins for autogenous arteriovenous fistula creation: A single-center retrospective study - Feng, Ruijia; Wang, Siwen; Chang, Guangqi; Zhang, Wayne W.; Liu, Qinghua; Wang, Xin; Chen, Wei; Wang, Shenming (Frontiers in Cardiovascular Medicine, 2023)
Objective Autogenous arteriovenous fistula (AVF) is recommended as the first choice for hemodialysis vascular access. A small-caliber vein is one of the independent risk factors for AVF maturation and patency. However, the specific threshold is still unclear, making it difficult to accurately determine whether these vessels are suitable for AVF creation. Design This is a single-center retrospective study. Method Patients who underwent AVF creation in our medical center between January 2020 and September 2022 and satisfied the eligibility criteria were included in this retrospective study. Logistic regression analysis was performed to identify risk factors for functional maturation and additional intervention. The optimal cutoff value was determined based on the receiver operating curve (ROC) and the Youden index. Kaplan–Meier analysis was utilized in further patency rate comparisons. Result A total of 125 forearm AVFs were created in 121 patients with end-stage renal disease (ESRD). The mean age was 53.88 ± 15.10 years. Preoperative vascular Doppler ultrasound (DUS) was conducted and recorded in 106 cases (84.80%). The mean targeted artery and vein diameters were 2.17 ± 0.54 and 1.71 ± 0.75 mm, respectively. Small-caliber vein is the risk factor for functional maturation failure (OR = 0.256, 95%CI [0.06–0.75], p = 0.033) and additional intervention (OR = 0.306, 95% CI [0.09–0.78], p = 0.031). The optimal cutoff value is 1.35 mm (augmented) when specificity and sensitivity reach 80 and 63.7%, respectively. The AVFs with a vein diameter of more than 1.35 mm (augmented) showed higher patency rates (p < 0.01). Conclusion After comprehensive DUS evaluation, intraoperative hydrodilation, postoperative active exercise and intensive DUS detection, and application of balloon-assisted maturation, if necessary, using a vein more than 1.35 mm (augmented), could achieve satisfactory functional maturation and postoperative patency in AVF formation.